Preparedness of Tsunami Disaster in Pandeglang Region Due to The Activity of Mount Krakatau - Ningtyas, Nadya Nur; Satyarno, Iman; Triatmadja, Radianta (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2022)
Pandeglang Regency is one of the areas with the most building damage in The 2018 Anak Krakatau Tsunami. The tsunami in 2018 was caused by the activity of Anak Krakatau Volcano in the form of an avalanche of material on the volcano’s cliffs. The subdistricts in Pandeglang Regency affected by the tsunami were Carita Subdistrict, Labuan Subdistrict, and Panimbang Subdistrict. This research evaluates potential damage to buildings to determine the condition of the existing land, determines an evacuation route to a temporary evacuation site (TES), and simulates a tsunami evacuation using this evacuation route. Parameters of run-up height and building type are used as parameters for assessing building damage. The determination of TES is influenced by run-up height, elevation, and distance from the shoreline. Evacuation route planning and evacuation simulation are based on the assumed number of evacuees and the scenario of a tsunami evacuation. The results showed moderate damage to buildings in Carita Subdistrict, Labuan Subdistrict, and Panimbang Subdistrict. The examination of existing land as TES, namely Carita Vacant Land, Carita 1 Middle School, LDII Labuan Mosque, Labuan Shelter Building, Panimbang Vacant Land. According to the tsunami evacuation scenario during the day, evacuation time results for 25-30 minutes with an average speed of > 1 m/s. The tsunami evacuation time at night is free of obstacles or with obstacles for 50-85 minutes with an average speed of 1 m/s. The tsunami evacuation time at night is full of free and obstacle-free tours for 60-100 minutes with an average speed of 0.5 m/s. Evacuation time based on simulation results is compared with evacuation time calculated by ETA and other studies as data validation to determine the probability of community preparedness in the Pandeglang Regency. The preparedness community in Pandeglang Regency is in the ready category by 25% in the Carita subdistrict, Labuan subdistrict, and Panimbang Subdistrict.